Digital filter bank based energy detector for spectrum sensing in wireless communication receivers - Chong, Chee Huat. (2012)
Electromagnetic scarcity in the wireless communication networks led to the idea of dynamically exploring the frequency spectrum opportunities with feature to reliably determine the portions of underutilized frequency band which may be used for communications. This spectrum sensing requires wireless network receiver equipped with spectrum analyzing feature. Digital filter bank can be used as a tool for spectrum analyzing.The spectrum sensing in this report focuses on energy based sensing. This report presents the theories used in digital filter bank design of a receiver, implementation of filter bank design and energy detection, and some statistical analysis on the performance of detection.